The Effect of Charades Game on Vocabulary Mastery of The Eleventh Grade Students at SMA Negeri 6 Pematangsiantar - Ruth Monika Simanjuntak; Sinurat, Bloner; Berthony Manalu, David (Innovative: Journal Of Social Science Research, 2024)
The aim of this research is to assess the impact of the Charades Game on vocabulary mastery among eleventh-grade students at SMA Negeri 6 Pematangsiantar. This study employs a quasi-experimental design, focusing on the use of the Charades Game as a method to enhance students' vocabulary skills. The population consists of 270 eleventh-grade students, with the sample divided into two classes: the experimental class (XI 7) with 30 students using the Charades Game, and the control class (XI 8) with 30 students receiving conventional instruction. Data analysis was conducted using the Paired test, revealing a significance (2-tailed) value of 0.000, which is less than 0.05. Consequently, the alternative hypothesis (Ha) is accepted while the null hypothesis (Ho) is rejected. Thus, it can be concluded that the Charades Game has a significant effect on the vocabulary mastery of eleventh-grade students at SMA Negeri 6 Pematangsiantar.